Managing NON-DIAGNOSTIC biopsies in musculoskeletal tumours in a specialist centre: Deciding on the algorithm. Issue 5 (May 2021) - Tamvakopoulos, George S.; Rose, Barry; Saifuddin, Asif; Skinner, John A.; Pollock, Robin
Abstract: Introduction: Core needle biopsy is an effective method of obtaining tissue diagnosis. However, a diagnostic dilemma arises when lesional tissue is non-diagnostic which obviates considering radiological guided re-biopsy (RB) or an open surgical biopsy but the question raised is which serves as a better diagnostic tool. Patient and methods: We retrospectively reviewed data from a prospectively collected database of 4516 core needle biopsies performed in our specialist musculoskeletal tumour centre over a 6-year period. Our aim was to evaluate the management of non-diagnostic biopsies (NDB) and establish a safe and accurate diagnostic strategy in the presence of a NDB. Results: Two hundred fifteen (4.8%) NDB cases with complete follow-up were identified. Of these 157 (73%) were treated definitively on the basis of imaging and 58 (27%) had a RB, 48 (83%) of which led to a positive histological diagnosis. The remaining 10 were again non-diagnostic giving a total of 167 patients being treated definitively without a tissue diagnosis. The sensitivity and specificity for multidisciplinary team (MDT) assessment as a diagnostic tool was 0.75 and 0.88 respectively while that for RB was 0.91 and 0.9. Conclusion: Re-biopsy after first non-diagnostic core needle biopsy offers high sensitivity and specificity, especially in the presence of malignancy. In the absence of tissue diagnosis, however, MDT assessment is also highly accurate and a safe strategy in managing this complex group of patients. Level of evidence: Diagnostic Level III.